Expedition to kalunga historical and cultural heritage site: An experience report - De Castro Santos Paim, Ricardo; De Paula, Luiza Gabriella Ferreira; Cardoso, Waltuir Silva; Rocha, Tarik Fernandes Gonçalves; Ribeiro, Amanda Lopes; Soares, Débora Moreira; Barros, Natália; Santos, Fabrício Carrião Dos; Ferreira, Heleno Dias; Gomes-Klein, Vera Lúcia; Soto-Blanco, Benito; De Oliveira-Filho, José Paes [UNESP]; et al. (Historia Ambiental Latinoamericana y Caribena - HALAC, 2023)
The Kalunga Historical and Cultural Heritage Site (SHPCK) is located in the northeast of Goiás and is considered one of the best-preserved areas of native Cerrado in all of Brazil. This is due to local geographic characteristics and mainly to the sustainable character of agricultural production by the traditional peoples who inhabit the region. In addition to having a vast preserved territory, the Kalungas have unique traditional knowledge about local plants. Due to biodiversity, they have access to herbal plants that can be used in human and animal food. However, the number of species of toxic plants may also considered high. With this report we aim to describe the unique experience that was the Expedition to the Kalunga Historical and Cultural Site and Heritage, as well as to emphasize the importance of the toxic plants of the Cerrado and the appreciation of traditional knowledge.
Expedição ao Sítio Histórico e Patrimônio Cultural Kalunga: um Relato de Experiência
Keywords: Cerrado; Curraleiro; Preservation; Quilombolas; Toxic plants